“I never really thought I would become a leader.” : art leaders’ perceptions of leadership roles and competences in the precarious structures of the Finnish independent arts sector - Hyle, Oula (Taideyliopiston Sibelius-Akatemia, 2026)
Recent research on the Finnish arts and cultural field has highlighted the precarious, and hybrid work structures, and expanding competence demands among cultural and arts professionals. This thesis contributes to this body of research by examining leadership practices under the Finnish independent art sector’s precarious structures. The study asks, how leaders emerge in their positions, and how these structural conditions shape and affect the leadership roles of the sector’s leaders. The study is based on six qualitative interviews conducted in the fall of 2025. The interviewees were individuals working in leadership positions in organisations operating outside the Finnish statutory state subsidy system. The analysis explores how these leaders define their leadership roles, assess their capabilities and competences to perform in them, and articulate the challenges and support needs associated with their work. In addition, the study evaluates the ways in which artistic, managerial, and organisational responsibilities are combined within individual roles. The thesis addresses the following questions through thematic analysis: How do leaders in the independent arts sector perceive and construct their leadership roles, and what kinds of competences, challenges, and expectations are associated with these roles. These questions are examined within the broader Finnish cultural policy and labour market context. The findings highlight the inherently hybrid and fluid nature of leadership in the independent arts sector. The study’s leadership roles were formed through unplanned career paths, either through founding an organisation or applying to a position with unclear expectations, often with no previous education or experience in leadership. The leadership roles were characterised by overlapping responsibilities, including artistic direction, organisational management, fundraising, and personnel supervision. The leaders systematically reported limited resources, insufficient time for supervisory tasks, and a lack of formal preparation for their responsibilities. A central contradiction emerged from this notion. While leadership roles had expanded in scope and complexity, the structural conditions of the sector constrained leaders’ ability to fully develop and perform their roles. As a result, leadership was shaped by continuous resourceless navigation between artistic values, organisational survival, and external expectations. The study contributes to a more nuanced understanding of leadership in hybrid arts organisations and highlights the need for stronger structural support, and professional recognition for the Finnish independent art sector’s leaders, and development of leadership education within the arts education.
Keywords: vapaa taidekenttä; Finnish independent art sector; leadership in arts; contemporary leadership models; johtaminen; johtajuus; taideala; organisaatiot; kulttuuriala; johtajat; taidehallinto; kulttuuripolitiikka; työhyvinvointi; cultural policy; fi=taidehallinto|sv=Arts Management|en=Arts Management|